The Use of Show and Tell Method to Teach English Speaking Skill - Sela, Sela; Rosnija, Eni; Wardah, Wardah (Journal of English Education Program, 2025)
This study aims to determine the effectiveness of the shadow and tell method in teaching English-speaking skills to eighth-grade students. Using the Show and Tell method, students are given the opportunity to explain an item that is engaging in increasing their interest in practicing speaking in class. A pre-experimental research design was used with one group pre-test and post-test involving 30 students. The sample was chosen by applying cluster random sampling technique. The data of students"™ achievement in speaking were collected through pre-test and post-test. These data were quantitatively analyzed, and the results showed that the t-test was higher than the t-table, and the effect size score indicated that the Show and Tell method had a strong effect. The results revealed that the Show and Tell method can be used to teach students"™ English-speaking skills. Using objects such as photos and people, the researcher found that students were engaged in speaking English because they were using things they enjoyed, such as classroom items, classmates, or favorite animals. As a result, teaching English speaking skill to students through the Show and Tell method can be enjoyable.